2009
DOI: 10.1242/jcs.036103
|View full text |Cite
|
Sign up to set email alerts
|

Role of syntaxin 18 in the organization of endoplasmic reticulum subdomains

Abstract: In Syn18(390)-transfected cells, we frequently (40-50% of cells at 72 hours after transfection) observed large patches positive for an ER membrane protein, Bap31 (Annaert et al., 1997) (Fig. 1B, middle row, left). Albeit much less frequently, similar patches were observed in cells transfected with the less efficient siRNA Syn18(770) (bottom row, left), suggesting that the redistribution of Bap31 is a consequence of syntaxin 18 depletion, and not a consequence of off target effect of Syn18(390). The different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 77 publications
6
45
1
Order By: Relevance
“…The ultrastructure of the anomalous tubuloreticular ER cluster demonstrated in the present study rather resembles that of the random tubular ER patches described in recent two studies (20,47). One of these two studies revealed anomalous ER patches in HeLa cells in which an ER-related soluble NSF attachment protein receptor (SNARE) protein, syntaxin 18, is depleted by knockdown with specific siRNAs (20).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The ultrastructure of the anomalous tubuloreticular ER cluster demonstrated in the present study rather resembles that of the random tubular ER patches described in recent two studies (20,47). One of these two studies revealed anomalous ER patches in HeLa cells in which an ER-related soluble NSF attachment protein receptor (SNARE) protein, syntaxin 18, is depleted by knockdown with specific siRNAs (20).…”
Section: Discussionsupporting
confidence: 78%
“…One of these two studies revealed anomalous ER patches in HeLa cells in which an ER-related soluble NSF attachment protein receptor (SNARE) protein, syntaxin 18, is depleted by knockdown with specific siRNAs (20). Syntaxin 18 is localized in the ER, and is thought to be involved in retrograde transport from the Golgi to the ER as well as homotypic ER membrane fusion (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of Syn18 causes remarkable aggregation of the smooth ER membrane, although rough ER membranes are relatively intact (Iinuma et al, 2009). Knockdown of BNIP1 resulted in the loss of the three-way junction of the peripheral ER (Nakajima et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…3C). Finally, syntaxin-18, a syntaxin member resided on the ER, was depleted in Hela cells by introducing siRNA oligo duplex against syntaxin-18 as previously described (Iinuma et al, 2009). When the treated cells were roughly fractionated to the cytosol and membrane fractions, depletion of syntaxin-18 hardly affected the subcellular distribution of α-taxilin (Fig.…”
Section: Association Of α-Taxilin With Intracellular Components As Amentioning
confidence: 98%